2014
DOI: 10.1186/1471-2407-14-78
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 promotes tumor cell proliferation through AR involving the Notch pathway in endometrial cancer

Abstract: BackgroundIncreasing evidence suggests that forkhead box A1 (FOXA1) is frequently dysregulated in many types of human cancers. However, the exact function and mechanism of FOXA1 in human endometrial cancer (EC) remains unclear.MethodsFOXA1 expression, androgen receptor (AR) expression, and the relationships of these two markers with clinicopathological factors were determined by immunohistochemistry analysis. FOXA1 and AR were up-regulated by transient transfection with plasmids, and were down-regulated by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 47 publications
0
60
1
Order By: Relevance
“…3E). Furthermore, additional motifs were identified for transcription factors previously described to be involved in endometrial cancer, including androgen receptor (35), progesterone receptor (36), RORB (37), as well as SOX proteins (38). Cumulatively, these data implicate that FOXA1 binds to ERa sites in tamoxifen-associated endometrial cancer that are potentially co-occupied by other transcription factors.…”
Section: Genomic Interactions Of Foxa1 and Era In Endometrial Tumor Smentioning
confidence: 89%
“…3E). Furthermore, additional motifs were identified for transcription factors previously described to be involved in endometrial cancer, including androgen receptor (35), progesterone receptor (36), RORB (37), as well as SOX proteins (38). Cumulatively, these data implicate that FOXA1 binds to ERa sites in tamoxifen-associated endometrial cancer that are potentially co-occupied by other transcription factors.…”
Section: Genomic Interactions Of Foxa1 and Era In Endometrial Tumor Smentioning
confidence: 89%
“…In our previous study, we found that FOXA1 suppressed the progression of estrogen receptor (ER)-positive EC, which was consistent with other studies (14,18). We also found that FOXA1 promoted cell proliferation via the androgen receptor (AR) and activated Notch pathway in ER-negative, AR-positive EC (19). Thus, FOXA1 is a bifunctional cancer-associated gene, which is oncogenic or tumor suppressive in a context-dependent manner.…”
Section: Discussionmentioning
confidence: 75%
“…On the other hand, Sasaki and coworkers reported that AR was not detected in 79% of endometrial carcinomas, although their cases included several unknown histological types (Sasaki et al 2000). Qiu and coworkers recently reported AR-highly expressing cells in 50 of 76 cases (66%) of endometrial carcinoma (Qiu et al 2014). In our previous study, AR immunoreactivity was detected in the nuclei of carcinoma cells and the number of positive cases was 39/44 (89%) (Ito et al 2002).…”
Section: Androgen Receptor Expressionmentioning
confidence: 95%
“…The expression of AR in endometrial carcinoma has been detected in several studies (Horie et al 1992, Sasaki et al 2000, Ito et al 2002, Qiu et al 2014. The number of cases was small (n = 4), but Horie and coworkers reported that all specimens of endometrial carcinoma tissues examined expressed AR (Horie et al 1992).…”
Section: Androgen Receptor Expressionmentioning
confidence: 99%
See 1 more Smart Citation